Predictive value of neutrophil-to-lymphocyte ratio for long-term adverse outcomes in cirrhosis patients post-transjugular intrahepatic portosystemic shunt - Qian Zhang; Zi Xu; Li Long; Xinhua Luo; Rongpin Wang; Kangshun Zhu (Scientific Reports)
Abstract The neutrophil-to-lymphocyte ratio (NLR) may predict outcomes in end-stage liver disease, but its value after transjugular intrahepatic portosystemic shunt (TIPS) is unclear. This study explored the link between NLR and long-term outcomes in decompensated cirrhosis patients post-TIPS. We retrospectively analyzed 184 patients treated between January 2016 and December 2021, noting demographic data, lab results, and follow-up outcomes, including liver transplantation or death. Cox regression, adjusted for various factors, showed that NLR is an independent predictor of post-TIPS progression (HR 1.665; 95% CI 1.149–2.414; P = 0.007). Patients were divided into tertiles based on NLR. The medium tertile had a 3.51-fold increased risk of progression compared to the lowest (HR 3.510; 95% CI 1.104–11.153, P = 0.033), and the highest tertile had a 5.112-fold increase (HR 5.112; 95% CI 1.653–15.806, P = 0.005). This suggests that NLR is a valuable prognostic marker for long-term progression in these patients, highlighting the role of systemic inflammation.